Hubungan Peer Attachment dengan Loneliness pada Mahasiswa Perantau Universitas Negeri Padang - Suci Ramadhani; Frischa Meivilona Yendi (International Journal of Applied Counseling and Social Sciences, 2026)
The phenomenon of students living away from home is becoming increasingly common among today’s college students. They are vulnerable to loneliness due to the challenges they face while living far from home, including homesickness, distance from family, and the need to adapt to a new environment. While previous studies have examined peer attachment and loneliness separately among general student populations, empirical evidence linking these two variables specifically among migrant students in Indonesian higher education particularly at Universitas Negeri Padang (UNP). This study aims to describe peer attachment and loneliness, as well as to examine the relationship between the two, among 384 out-of-town students from the class of 2024 at Universitas Negeri Padang, selected using purposive random sampling. This study employs a quantitative approach with a descriptive correlational method. Data were collected using a modified version of the Inventory of Parent and Peer Attachment (IPPA) and the UCLA Loneliness Scale Version 3, both of which had passed validity and reliability tests, and were analyzed using descriptive statistics and Spearman's rank correlation test. The results showed that peer attachment among out-of-town students was in the high category, while loneliness was in the low category, with a significant negative relationship between the two variables (r = -0.700, p = 0.000, p < 0.05), classified as strong. These findings indicate that the higher the peer attachment, the lower their levels of loneliness; thus, peer attachment is one of the factors related to loneliness among migrant students. Therefore, the findings of this study can contribute to the field of guidance and counseling in designing programs that emphasize the importance of peer-based interventions to help reducing feelings of loneliness among migrant students.